Literature, film and television - coexistence, antagonisms, influences - Đorđević Milentije M. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
This paper deals with the issue of the position of literature in relation to film and television in present times. The beginning of the 20th century was marked by the appearance of new media such as film and radio, and later on television. These new media in essence stemmed from literature, but at a certain moment assumed the rival role to the art on which they were based. In this century, literature, film and television coexist, operate in parallel, and at certain points intertwine and mutually upgrade in artistic terms.